Lack of Rev7 function results in development of tubulostromal adenomas in mouse ovary. (5th September 2015) - Abbasi, Abdolrahim; Khalaj, Maryam; Akiyama, Kouyou; Mukai, Yoshiyuki; Matsumoto, Hirokazu; Acosta, Tomas J.; Said, Neveen; Yoshida, Midori; Kunieda, Tetsuo
Highlights: Rev7 mutant mouse lacks oocyte and develops tubulostromal adenomas in ovary. Rev7 mutant mouse shows significantly increased blood gonadotropin level. Cells of Rev7 mutant mouse accumulate DNA damages in their nuclei. Abstract: Rev7 is a subunit of Polζ, one of the translesion DNA synthesis (TLS) polymerases involved in DNA damage repair. We recently found that Rev7 is also essential for germ cell development in mouse. In the present study, we found the development of ovarian tumors in Rev7 mutant mouse, suggesting the involvement of TLS deficiency in the etiology of ovarian tumor. The Rev7 mutant mice showed complete lack of oocytes and follicles in the ovary. The lack of follicles causes a significant increase of gonadotropin level and an increase in the proliferation of ovarian cells. As a result, the weight of the ovaries of Rev7 mutant mice increased with age and they developed tubulostromal adenomas. However, the remarkable overgrowth of ovaries occurred after gonadotropin level decreases at older ages, suggesting gonadotropin-independent progression of the ovarian tumors. In addition, the Rev7 mutant fibroblasts and ovarian cells showed significant accumulation of DNA damage. These findings suggest that not only increased gonadotropin levels but also lack of DNA damage repair function could be responsible for the development of ovarian tumors in the Rev7 mutant mouse.